Life satisfaction, pro-activity, and employment - Alpaslan Akay; Gökhan Karabulut; Levent Yilmaz (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Using longitudinal data from the German Socio-Economic Panel (GSOEP), this paper investigates how pro-active time-use (e.g., in sports/arts/socializing) relates to subjective well-being of the unemployed and their probability of finding a new job. Allowing for a variety of socio-demographic and -economic observed characteristics, we find that pro-activity is negatively associated with the well-being loss upon unemployment. That is, the negative unemployment shock on their well-being is mitigated through various stress-reducing activities including, in particular, art participation, socializing, going on trips, and visiting a church. We also find that the probability of returning to the labor market later is positively associated with pro-activity during the unemployment period. The results are robust to various checks including estimators, measures, and individual personality characteristics which can correlate with time-use activities.
Keywords: I31; J64; J69; 330; Life satisfaction; pro-activity; employment; labor markets